Analisis Kebutuhan Pengembangan Bahan Ajar Elektronik Mata Kuliah Desain dan Strategi Pembelajaran di IKIP Budi Utomo - Hartati, Tri Asih Wahyu; Lufthansa, Luthfie; Malahayati, Eva Nurul (Efektor, 2020)
Teaching materials are one of the factors that can affect the smoothness of the learning process and student learning outcomes. Design and Learning Strategies courses are compulsory subjects taught at the S1 level of the Health and Recreation Physical Education Study Program at IKIP Budi Utomo. Teaching materials for Design and Learning Strategies courses that are currently used are limited to printed teaching materials which contain material descriptions. The purpose of this study was to determine the needs of students in learning Design and Learning Strategy Subjects, especially in providing learning resources at IKIP Budi Utomo. This research method is descriptive quantitative. The research subjects were students of the 2018 IKIP Budi Utomo Recreation and Physical Education Study Program. The sample was randomly selected. They are collecting data through interviews with Subject Management Lecturers and student questionnaires. The results of the interviews show that the teaching materials used so far are still limited to printed teaching materials which contain descriptions of design materials and learning strategies in general, there are no specific examples of Physical Education learning designs and also important concepts of Physical Education learning. The results of the student need questionnaire analysis show that: 1) the teaching materials needed by students are in the form of electronic teaching materials (e-books), 2) the material in the teaching materials is material related to the specifications of the field of science, namely physical education learning.